Quantum mechanics - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
For centuries, philosophers and spiritual thinkers have struggled with the concept of free will. Do we, in fact, choose our thoughts, actions and journey through this life? Or are we merely an aggregation of particles that react and respond based purely on biological and psychological factors. Join us as we explore the fine relationship between free will and Quantum Mechanics.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi
DVD format